The Effect on the Immune System in the Human Body Due to COVID-19: An Insight on Traditional to Modern Approach as a Preventive Measure - Jugal Sutradhar; Bapi Ray Sarkar (Korean Pharmacopuncture Institute, 2021)
The COVID-19, the most infectious pandemic disease arising due to SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) has caused huge issues globally. In this review, we discuss the impact of COVID-19 on the immune system of the human body and the protective mechanisms of the host immune system opposing viral infections. Here, we summarize the effect of the pandemic of the novel coronavirus disease on the immune system such as sleep and Behavioral Immune System (BIS) together with consideration of researcher's observation points of view. We draw particular attention to recent up-to-date reports concerning COVID-19 drugs as well as information about the landscape document for COVID-19 vaccines released by WHO (World Health Organization), and some adverse events of COVID-19 vaccination. Additionally, can take part in the preventive appraise in opposition within this pandemic severe COVID-19 infections disease may affect some outcome in physical exercise, physical movement, healthy diets, and good nutrition are significant for supporting the immune systems and summarize AYUSH (Ayurveda, Yoga and Naturopathy, Unani, Siddha, and Homeopathy) Indian medicinal systems guidelines for immunity boosting procedures during COVID-19 pandemic.